FSKKP final year student-supervisor matchmaking expert system - Aishah, Che Mohd (2011)
FSKKP Final Year Student-Supervisor Matchmaking,Expert System is build to help students to assess the ability of supervisors follow by their chosen field.Using this system,it also will help student to choose their correct supervisor and thus making their final year projects will be established under the guidance of supervisors who have the same field with the title of their project. Besides,this will strengthen the secure of data storage. It is developed using Adobe Dreamweaver and PUP SQL;key in data using insert and delete function,relocate required items using search function and update of progress are acknowledge faster.FSKKP Final Year Student-Supervisor Matchmaking Expert System consist of 6 main modules which are'Login,'Home','Publication','Research''Supervision', 'Education','Area of Expertise','Teaching Specialist'and another extra modules that display general information. In this project,the algorithm is used to get the highest index of lecturer.